Identification profile with extensive and semi-intensive beef cattle production system in District Sorong, Southwest Papua Province - Saputra , Indra; Prasetia, Muh. Andika; Anggriani , Rini; Lena , Mirza; Aditama, Ryzal Satria; Wijaya, Andi Iksan; Sulfiar, Ahmat Endang Two (Fakultas Peternakan Universitas Papua, 2025)
The farmes in Southwest Papua, have started using the semi-intensive farming system for Beef Cattle rearing in recent decades. This study aimed to determine the profile profile of beef cattle farmers under with extensive and semi-intensive farming systems in Sorong Regency, Southwest Papua Province. This research was conducted from January to March 2024 using the Participatory Rural Appraisal method, which is an approach that involves family members or individuals to analyze the reality of the living conditions they live in. This research involved 100 breeders divided into 60 extensive farmers and 40 semi-intensive farmers who were selected using purposive sampling. Data were described quantitatively and analyzed using the independent T test. The results showed that the age of farmers in the semi-intensive system was younger but their farming experience was longer in the extensive system (P<0.05). The motivation for keeping livestock as savings, the main livelihood and the function of livestock as a fertilizer producer are not significantly different, but breeders in different rearing systems view that the motivation for keeping livestock as savings is still very important. The number of cows in the extensive system was higher than in the semi-intensive system (P<0.05). It was concluded that farmers with extensive and semi-intensive farming systems use cattle more for savings and insurance purposes compared to breeders whose background is in animal husbandry as their main occupation and fertilizer producer